Political Connections, Female on Board, dan Audit Committee dalam Praktik Earnings Management: Apakah CEO Tenure Memperkuat Hubungan Tersebut? - Advensia Tian; Hartono Hartono; Dedi Haryadi (Yayasan Pendidikan Penelitian Pengabdian Algero, 2026)
Economic development in Indonesia has intensified corporate competition, increasing pressures on financial reporting transparency. Practices such as earnings management can obscure financial statement credibility and diminish stakeholder trust. Based on Agency Theory and Upper Echelons Theory, this study examines the effect of political connections, board gender diversity (female on board), and audit committee independence on earnings management, while evaluating the moderating role of CEO tenure. Focusing on basic materials subsector companies listed on the Indonesia Stock Exchange (IDX) from 2020 to 2024, the study employs panel data analysis via the Fixed Effect Model (FEM) with robust standard errors to address potential diagnostic issues. Firm size and time dummies are specified as control variables. The empirical findings reveal that political connections significantly increase discretionary accruals when CEO tenure is long, demonstrating that CEO power amplifies political influence over financial reporting. Conversely, female board representation and audit committee independence do not directly constrain earnings management, reflecting potential tokenism and formalistic governance structures. This study provides critical insights for capital market regulators and corporate governance practitioners in emerging markets.